The role of social norms in practicing amr ma’ruf nahi munkar: A case study at Sabilurrasyad Pesantren - Handayani, Triana; Bakri, Maskuri; Hakim, Dian Mohammad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study explores the application of the concept of